Temporalities of speculation and discounting in the twentieth century - Jamie Pietruska (Finance and Society)
This article reviews Paul Crosthwaite’s Speculative Time: American Literature in an Age of Crisis (2024) and Liliana Doganova’s Discounting the Future: The Ascendancy of a Political Technology (2024), situating them within recent scholarship on a future-oriented, speculative, and economic subject. It focuses on the relationship between financial speculation and temporalities in the twentieth century, specifically on futures and the politics of value in American literature and the calculating technology of discounting. These books bridge what have been two distinct scholarly approaches to studies of capitalist futures: a theoretical focus on futures as cultural imaginaries or narratives of economic action and a material emphasis on practices for anticipating futures and managing risk. The article concludes with a discussion of power and profit in speculation and discounting, emphasizing inequitable access to speculative futures, and suggests that the multidirectional, nonlinear, recursive mode of financialized temporalities in these books might offer a guide to imagining and creating more just futures for us all.